Online learning readiness and satisfaction in English as a foreign language at higher education context: the moderating role of engagement - Ertan Altınsoy; Serkan Boyraz (Frontiers in Psychology)
IntroductionWith the rapid advancement of technology and the unexpected outbreak of COVID-19, educational institutions worldwide were compelled to shift to e-learning, especially in the field of foreign language instruction such as English as a Foreign Language (EFL). While online learning environments offer advantages like flexibility, accessibility, and interactivity, challenges persist in sustaining student engagement and ensuring satisfaction. This study was prompted by low student attendance in online EFL classes at a public university in Türkiye. The primary aim was to explore the mediating role of Engagement in Online Learning (EOL) in the relationship between Online Learning Readiness (OLR) and Online Learning Satisfaction (OLS).MethodThe study employed a quantitative research design, involving a sample of 945 associate and undergraduate students enrolled at a state university in Türkiye. Standardized instruments were used to measure OLR, EOL, and OLS. Data were analyzed using correlation and mediation analyses, along with tests for moderation by demographic variables such as age and gender.Results and discussionFindings indicated a medium-level, positive, and statistically significant relationship between students’ OLR and their OLS. A strong positive correlation was also found between OLR and EOL. Furthermore, engagement (EOL) was shown to significantly mediate the relationship between readiness (OLR) and satisfaction (OLS), suggesting that students’ active participation plays a crucial role in achieving satisfaction in online learning environments. Age was not a moderating factor in the readiness-satisfaction link, whereas gender was found to have a significant moderating effect. Additionally, a moderate, positive, and significant relationship was observed between engagement and satisfaction. These results highlight the importance of fostering engagement to enhance students’ online learning experiences and outcomes in EFL contexts.